2014
DOI: 10.1371/journal.pone.0115395
|View full text |Cite
|
Sign up to set email alerts
|

Elevation-Related Variation in Leaf Stomatal Traits as a Function of Plant Functional Type: Evidence from Changbai Mountain, China

Abstract: Understanding the variation in stomatal characteristics in relation to climatic gradients can reveal the adaptation strategies of plants, and help us to predict their responses to future climate changes. In this study, we investigated stomatal density (SD) and stomatal length (SL) in 150 plant species along an elevation gradient (540–2357 m) in Changbai Mountain, China, and explored the patterns and drivers of stomatal characteristics across species and plant functional types (PFTs: trees, shrubs, and herbs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 46 publications
3
38
1
Order By: Relevance
“…a). These findings suggest that the response of stomatal frequency differs among different plant life forms (Wang et al ., ). Regression analysis revealed that the stomatal frequency initially increased and then decreased with increasing elevation (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…a). These findings suggest that the response of stomatal frequency differs among different plant life forms (Wang et al ., ). Regression analysis revealed that the stomatal frequency initially increased and then decreased with increasing elevation (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…It is known that environmental changes can influence stomatal development (Fraser et al, 2009;Hill et al, 2015). Thus, an elevation gradient also provides a powerful setting in which to test the responses of stomatal frequency to changing environmental conditions because large changes in environmental factors can occur over short distances (Qiang et al, 2003;Wang et al, 2014). Studies of the effects of altitude on SD have shown a range of responses along elevation gradients, including decreases (Schoettle & Rochelle, 2000), increases (Kouwenberg et al, 2007), and no change (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between our results and theirs could be a consequence of us looking at a wider geographic area rather than individual populations, or a difficulty in accurately counting and measuring stomata on herbarium specimens. It is also noteworthy that abiotic factors can influence stomatal size and density along elevational, temperature, and water gradients (Körner & Cochrane, 1985;Kluge & Kessler, 2007;Wang & al., 2014). Such variation is likely in baobabs given evidence of higher stomatal density and smaller guard cells in high-temperature and low-rainfall areas in Benin, though this relationship was not also found in Malawi (Sanchez, 2010;Sanchez & al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic plasticity is influenced by several environmental factors such as temperature, light intensity, water availability and atmospheric levels of carbon dioxide (Bradshaw & Hardwick, 1989;Sultan, 2000). Stomatal density is a suitable phenotypic characteristic for understanding the long-term adaptation and short-term response of plant species to changing environmental conditions at large spatial scales (Hetherington & Woodward, 2003;Bresson et al, 2011;Wang et al, 2014). Furthermore, studies exploring stomatal characteristics such as stomatal density may give information about the degree to which plants that are grown outside their natural habitats adapt to new environmental conditions (Sevik et al, 2017).…”
Section: Introductionmentioning
confidence: 99%